ANALISA KINERJA DAN TINGKAT KEPUASAN PELANGGAN PDAM KOTA UNGARAN KABUPATEN SEMARANG - Setiabudi Bambang; Suharyanto Suharyanto; Syafrudin Syafrudin (TEKNIK, 2012)
The need for water supply always increases with population growth and development of the region, demandingPDAM Semarang able to provide a better service to their communities.The issue of high rate of leak, the high discharge capacity untapped and range of services is still very low whichis a major problem for the Semarang District PDAM water supply for the City of Ungaran. Similarly on thequestion of the level of customer satisfaction and service performance should be analyzed so that companies canknow the goals and strategies in improving water services to the community.Customer satisfaction to water supply services, measured in terms of customer perception in the use of watersupply. The analysis showed that customer satisfaction in the category of high levels of satisfaction are stronglyinfluenced by water pressure, adequacy of water use, quality of complaints handling and accuracy of watermeter readings.The results of the performance assessment of water services which refers to two normative rules, namely No.47of 1999 Kepmendagri obtain the final value of 58.16 is included in the category of adequate and appropriatecriteria BPPSPAM obtain the final value of 2.055 is included in the healthy category.From the results of the performance analisia taps and customer satisfaction level analysis shows that there aresome indicators of corporate performance and customer satisfaction needs to be improved and enhanced.